1995
DOI: 10.1002/jmri.1880050515
|View full text |Cite
|
Sign up to set email alerts
|

Phased‐Array Magnetic Resonance Imaging of the Carotid Artery Bifurcation: Preliminary Results in Healthy Volunteers and a Patient with Aherosclerotic Disease

Abstract: A high resolution MR imaging technique using a custom designed flexible phased-array surface coil was developed to examine the wall of the carotid artery bifurcation in vivo. The phased-array consisted of two overlapping coils which increased the image signal-to-noise ratio at the depth of the carotid artery by approximately 70%, relative to a similarly sized single loop coil. The imaging protocol included a 2D T1-weighted (T1W) spin-echo scan and cardiac gated T2-weighted and proton density-weighted (PDW) fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 15 publications
2
43
0
2
Order By: Relevance
“…9,11,12,44,45 A misalignment of the imaging plane and the long axis of the vessel can lead to inaccurate cross-sectional images and lead to errors in wall thickness measurements and plaque imaging. Careful planning in this study minimized these errors.…”
Section: Possible Further Improvementsmentioning
confidence: 99%
“…9,11,12,44,45 A misalignment of the imaging plane and the long axis of the vessel can lead to inaccurate cross-sectional images and lead to errors in wall thickness measurements and plaque imaging. Careful planning in this study minimized these errors.…”
Section: Possible Further Improvementsmentioning
confidence: 99%
“…Previous studies demonstrated that phased-array coils provide better SNR than single-loop surface coils (6,11,12). The present study evaluates the performance of a quadrature-coil design in the depiction of the carotid bifurcation.…”
Section: Discussionmentioning
confidence: 97%
“…MRI HAS THE POTENTIAL to define atherosclerotic plaque components in vivo at the carotid artery (1)(2)(3)(4)(5)(6). Normally, the atherosclerotic plaque in the carotid artery has an averaged length of 2.0 -2.5 cm and the thickness in the axial plane is 5-10 mm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 The potential role of MRI for noninvasive assessment of plaque morphology and lesion burden quantification has been addressed in several investigations ex vivo and in vivo. [12][13][14][15][16][17][18][19][20][21][22][23][24] The appearance of plaque calcification has been described as uniformly dark in signal intensity on all MRI sequences. 18,25,26 However, there are other components of atherosclerotic plaque that may show decreased signal intensity on some or all pulse sequences; for example, solid cholesterol hydrate may be present and plaque lipids may exhibit T2 shortening secondary to liquid crystal behavior, depending on the lipid composition and cholesterol content.…”
mentioning
confidence: 99%